2015
DOI: 10.3889/oamjms.2015.058
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Amount of Anti-D Antibodies and IgG Subclasses with Severity of Haemolytic Disease of Foetus and Newborn

Abstract: AIM:The aim of this study was to investigate the influence of subclasses to IgG anti-D on the intensity of hemolytic disease of fetus and newborn (HDFN) at 45 fetuses/newborns with symptoms of mild and severe HDFN in Republic of Macedonia.MATERIAL AND METHODS:In retrospective and prospective studies, in a period of 10 years, from 2004 to 2014, there have been immunohemathology tests performed on 22 009 samples on serums of pregnant women.RESULTS:At 37.78% of the total number of tested patients, IgG1 and IgG3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…In order to obtain stronger phagocytosis reactions with a greater number of cells involved, we opsonized the erythrocytes with anti‐D antibodies. This model corresponds to the hemolytic transfusion reaction and to hemolytic disease of the fetus and newborn, in which spleen macrophages engulf erythrocytes (Basu et al, ; Velkova, ). The use of monocytes from the peripheral blood is suitable for predicting extravascular immune hemolysis in some recipients with rare alloantibodies, especially when it is difficult to find serologically compatible red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain stronger phagocytosis reactions with a greater number of cells involved, we opsonized the erythrocytes with anti‐D antibodies. This model corresponds to the hemolytic transfusion reaction and to hemolytic disease of the fetus and newborn, in which spleen macrophages engulf erythrocytes (Basu et al, ; Velkova, ). The use of monocytes from the peripheral blood is suitable for predicting extravascular immune hemolysis in some recipients with rare alloantibodies, especially when it is difficult to find serologically compatible red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty years ago, HDN was almost synonymous with RhD sensitization and was a common neonatal problem. Since then, other blood group antigens of the Rh system (C, c, E, e, Cw), and other blood group systems have come to light [3,10,15,19]. The introduction of anti-D prophylaxis and mandatory immuno-hematological screening 3 times during pregnancy [2] has significantly decreased the number of fatalities caused by Rhesus D (RhD) sensitization and its severe impact on infants and pregnant women [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies so far have reported various immunization rates among different study groups, ranging from 5% in the general population and a mean percentage of 1.6% in pregnant women worldwide [ 6 , 7 ] to up to 30% in multitransfused patients (myelodysplastic syndromes, thalassemia patients) [ 8 , 9 ]. Genetic heterogeneity between donor and recipient populations, differences in transfusion policies, and differences in the specificity and sensitivity of the test methods may account for the reported variation [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%